Terminologi Qur’ani tentang Manusia: Analisis Konseptual atas Makna, Karakter, dan Peran Eksistensial dalam Al-Qur’an - Samsul Hakim; Rawzalgina, Arthi Amalia (Kartika: Jurnal Studi Keislaman, 2026)
Human beings hold a distinguished position in Islam, as explained in the Qur’an. As creatures created by Allah, humans are endowed with intellect, spirit, and the freedom to conduct their lives, thereby bearing moral and spiritual responsibilities. The Qur’an employs various terms to describe human beings such as basyar, insan, bani Adam, and ‘abd each of which highlights different biological, psychological, and theological dimensions. Moreover, Islam assigns humans two primary roles: as khalifah (khalifatullah fi al-ard), responsible for managing the earth with justice, and as servants of Allah (‘abdullah), who are obliged to submit to and obey His commands. This study adopts a library research method by examining and analyzing various sources of literature, including Qur’anic exegeses, books, and scholarly journals that discuss the concept of humanity in Islam. The findings reveal that, according to the Qur’an, humans are not merely biological beings but entities endowed with moral, intellectual, and spiritual responsibilities. By understanding the Qur’anic concept of humanity, one may attain deeper insights into the essence of human existence, as well as the roles and responsibilities humans must uphold in both worldly life and the hereafter